Truptighna mahakashaya is the remedy for Functional Dyspepsia (AYUSHDHARA, 2023)
Functional dyspepsia (FD) is a clinical condition that brings the patient to the doctor with a wide range of symptoms. Many patients go on changing the consultants thinking that they are suffering with a complicated disease. The prevalence of FD is 20% worldwide. But, in India, the prevalence of FD ranges from 7-49% as per data published in one of the studies. Modern medical science treats the condition with PPI, H2 blockers, prokinetic drugs, Probiotics and many more to provide symptomatic relief. Likewise, Ayurveda, an age old health care system of India has developed its own way of treating this condition based on symptoms. Charaka has classified 500 drugs in 50 groups known as Maha kashaya. Each group of Maha kashaya consists of 10 drugs. Among these groups, a class known as Truptighna maha kashaya contains those drugs that relieve the early satiety and abdominal discomfort. But, the interesting fact is that these drugs have additional pharmacological actions that can be utilized to bring relief to the patients of FD of modern era. The drugs have 11 prominent actions that help relieving the symptoms and also prevent the complication of the condition. This class becomes a good alternative, appropriate, well-meant, nicely formulated remedy for functional dyspepsia.